Evidence of a stratospheric QBO modulation of tropical convection - Knaff, John A., author (Colorado State University. Libraries, 1993)
Evidence is presented of a modulation of deep tropical convection by the Stratospheric Quasi-Biennial Oscillation (SQBO) in convective anomalies, precipitation and pressure in the Western Tropical Pacific region. In particular, the SQBO, by creating differing amounts of upper tropospheric (200 mb) to lower stratospheric (50 mb) zonal wind shear, appears to modulate deep tropical convection. Results suggest that in the tropical West Pacific region, strong values of this vertical shear act to suppress convection, limit rainfall and often raise surface pressures. During the west phase of the SQBO, areas of least 200 mb to 50 mb shear are located in off-equator regions. In contrast, during the east phase of the SQBO, minimum 200 mb to 50 mb zonal wind shear is located along the equator. These differences result in convection being preferred off (on) the equator during the west (east) phase of the SQBO. Because the SQBO creates opposing patterns of this 200 mb to 50 mb zonal wind shear during the east and west phases, convection is modulated by each of these patterns for a prolonged (6-18 month) period, thus allowing time for gradual change in the West Pacific general circulation. The convection, rainfall, pressure, and circulation patterns associated with the differing phases of the SQBO are discussed along with a preliminary theory for these patterns. Furthermore, evidence is presented that the west phase of the SQBO favors cold ENSO events whereas the east phase favors warm ENSO events.
January 1993.
Also issued as author's thesis (M.S.) -- Colorado State University, 1992.
Keywords: Convection (Meteorology); Tropical meteorology